A Korean Patient with Lattice Corneal Dystrophy Type IV with Leu527Arg Mutation in the TGFBI Gene - Kim, Jinsun (The Korean Ophthalmological Society, 2014)
An 87-year-old woman visited our clinic for a scheduled cataract surgery. At the time of preoperative evaluation, slit lamp examination showed lattice-shaped and granular deposits with asymmetrical patterns in the stroma of both corneas. Genomic DNA samples of the patient, amplified by polymerase chain reaction, showed a single nucleotide substitution, c. 1580T>G (p.L527R), in the transforming growth factor-β-induced TGFBI gene. We also found two additional SNP mutations, c.1620T>C (p.F540F) and c.1678+23G>A, along with the well-known L527R mutation. This is the first report of lattice corneal dystrophy type IV with an L527R mutation outside of Japan, and could challenge the idea that L527R is caused by a mutation from a single Japanese ancestor.